2008
DOI: 10.2478/v10005-007-0030-y
|View full text |Cite
|
Sign up to set email alerts
|

Hamiltonian Unification of General Relativity and Standard Model

Abstract: The Hamiltonian approach to the General Relativity and the Standard Model is studied in the context of its consistency with the Newton law, the Higgs effect, the Hubble cosmological evolution and the Cosmic Microwave Background radiation physics. The version of the Higgs potential is proposed, where its constant parameter is replaced by the dynamic zeroth Fourier harmonic of the very Higgs field. In this model, the extremum of the Coleman--Weinberg effective potential obtained from the unit vacuum--vacuum tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…The scale-invariant variables and d-invariant evolution parameter as the dilaton zeroth mode D (τ ) are compatible with a definite d-invariant cosmological dynamics known as the Conformal Cosmology [9,10,11,12,13,14,15,16] that strongly differs from the heuristic phenomenology of the accepted Standard Cosmology [2]. Principles of the conformal symmetry, relativistic (frame) symmetry, and d-invariance of observables and the Dirac Hamiltonian approach to GR completely determine the finite volume generalization of Einstein theory [13,14,15,16]…”
Section: Dilatonic Variables In General Relativitymentioning
confidence: 97%
See 3 more Smart Citations
“…The scale-invariant variables and d-invariant evolution parameter as the dilaton zeroth mode D (τ ) are compatible with a definite d-invariant cosmological dynamics known as the Conformal Cosmology [9,10,11,12,13,14,15,16] that strongly differs from the heuristic phenomenology of the accepted Standard Cosmology [2]. Principles of the conformal symmetry, relativistic (frame) symmetry, and d-invariance of observables and the Dirac Hamiltonian approach to GR completely determine the finite volume generalization of Einstein theory [13,14,15,16]…”
Section: Dilatonic Variables In General Relativitymentioning
confidence: 97%
“…The cosmological dynamics of the Conformal Cosmology (CC) strongly differs from the heuristic phenomenology of the accepted Standard Cosmology (SC) including the ΛCDM (2) and (3) explain redshift by the permanent increase of all masses in the Universe [9,10,11,12,13,14,16]. The corresponding…”
Section: Cosmological Dynamics Of the Zeroth Dilaton Modementioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, Glinka et al [23] using quantum field theory methods showed that number of universes generated from stabilized vacuum is…”
Section: Linking Driving "Frequency" As a Results Of Change In Temperamentioning
confidence: 99%